Efficient rating of parametrical control, using statistical modeling method - Щапов, Павел Федорович; Камбаев, Иван Иванович; Тищенко, Иван Вячеславович (Eastern-European Journal of Enterprise Technologies, 2013)
This article shows us the use of statistical methods for the analysis of information systems, which are used to monitor violations of precision transducers. The purpose of the article is to discover opportunities of new information technologies for measuring transformations that are used to control the structural accuracy of transducers, when there are no samples of measured values. We consider two information structural models of outputs duplicated transmitters. Using of probabilistic and statistical models for the outputs of the converter duplicates allows us to estimate the residual variance of the signal and to identify the difference of these dispersions as an informative parameter. We can consider differential control method as a method of obtaining measurement data, because of the discrepancy in accuracy characteristics of duplicate transmitters. The theoretical explanation for the differential method of disassembling control information, where we can see the difference between the residual variance, is used in comparable structural transformations of models that are functionally dependent on the correlation properties of the output signals of the transducers. The results of the statistical modeling in information transformations, which were used for error control in random measurement signals are shown in the article.